ANALISIS KEMANDIRIAN BELAJAR DAN HABITS OF MIND SISWA PADA PEMBELAJARAN ASESMEN PORTOFOLIO - Rikizaputra Rikizaputra; Lufri Lufri; Andromeda Andromeda; Fatni Mufit (Postgraduate, University of Mataram, 2021)
Everyone is taught to live independently, independence is a pattern of life that is formed from the habits of various human habits. Habit of thinking is one of the causes. The habits of intelligent thinking of each individual are called habits of mind. Independence and habits of mind are the factors needed in the series of learning processes so that the problems faced by students are able to be resolved properly, becoming a problem in schools that students' learning independence is less honed because of the dominance of teachers in teaching. The purpose of this study was to determine the profile of students' learning independence and habits of mind. Conducted in 2020 in class X MIA SMAN 7 Pekanbaru. This research is a descriptive research type with a survey method. The instruments used were in the form of a questionnaire of learning independence and habits of mind with 30 items of positive and negative statements that have been validated on a 5-Likert scale ranging from strongly disagree (SD) to strongly agree (SA) With three questionnaire categories, there are 3, namely high (mean 4.41-5.00), moderate (mean 3.39-4.40), low (mean 1.00-3.38). The research data were processed by using descriptive percentages. The results showed that the independent learning in portfolio assessment learning was 3.60 in the medium category. The mean of students' habits of mind is 3.8 in the medium category